2015
DOI: 10.1093/jmcb/mjv014
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal proteins: functions beyond the ribosome

Abstract: Although ribosomal proteins are known for playing an essential role in ribosome assembly and protein translation, their ribosome-independent functions have also been greatly appreciated. Over the past decade, more than a dozen of ribosomal proteins have been found to activate the tumor suppressor p53 pathway in response to ribosomal stress. In addition, these ribosomal proteins are involved in various physiological and pathological processes. This review is composed to overview the current understanding of how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
491
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(530 citation statements)
references
References 196 publications
(217 reference statements)
20
491
0
4
Order By: Relevance
“…29 Although low doses of Act D have been studied in p53 cell system, it has been demonstrated that the selective inhibition of rRNA synthesis by Act D was able to cause a perturbation of cell cycle progression also in cells silenced of p53, but the molecular pathways by which this occurs has not been determined. 9 Here we show that low doses of Act D (5 nM) induce the expression of rpL3 and its release from the ribosome in p53 mutated and p53 negative cells (Fig. 1).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…29 Although low doses of Act D have been studied in p53 cell system, it has been demonstrated that the selective inhibition of rRNA synthesis by Act D was able to cause a perturbation of cell cycle progression also in cells silenced of p53, but the molecular pathways by which this occurs has not been determined. 9 Here we show that low doses of Act D (5 nM) induce the expression of rpL3 and its release from the ribosome in p53 mutated and p53 negative cells (Fig. 1).…”
Section: Discussionmentioning
confidence: 51%
“…Perturbations in processes such as rRNA synthesis, rRNA modification as well as ribosomal protein (r-protein) imbalance produce alterations in ribosome biogenesis and resulting in nucleolar stress, causing an accumulation of ribosome-free form of r-proteins. [9][10][11] In response to this event some r-proteins translocate from the nucleolus to the nucleoplasm where bind to (mouse double minute-2 homolog) MDM2 thus promoting p53 stabilization and subsequent p53 mediated cell cycle arrest or apoptosis. 12 Recent findings revealed novel stress response pathways, which function independently of p53 and still lead to cell cycle arrest and/or apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their primary function in ribosome biogenesis, many RPs have extraribosomal functions (Warner and McIntosh, 2009;Zhou et al, 2015). As suggested by Warner and McIntosh (Warner and McIntosh, 2009), the following criteria must be met to define extraribosomal functions of RPs: (i) interaction with some nonribosomal components of the cell; (ii) the interaction has physiological effects on cellular functions; (iii) the effects occur away from ribosomes; (iv) the effects do not influence protein synthesis.…”
Section: The Extraribosomal Functions Of Rpsmentioning
confidence: 99%
“…Another critical determinant of proper gene expression and cell survival is the presence and proper function of all 79 RPs that are found within eukaryotic ribosome (Zhou et al, 2015). Ribosome is a complex molecular machine that is primarily responsible for 6 translation and protein synthesis from messenger RNA (mRNA).…”
Section: Figure 1 Nuclear Envelope Budding In Drosophila Muscle Cellsmentioning
confidence: 99%